Typical Features of Politeness Strategy Performed by Anregurutta (Religious Leader in Pappandangan Maros District of South Sulawesi) - Arham Halwin Rani; Martin L. Manda; Abdul Hakim Yassi; Hamzah Machmoed (ELS Journal on Interdisciplinary Studies in Humanities, 2020)
Politeness has been considered as a core dimension of social interaction regardless of culture and ethnicity and is a predictor of good etique to prevent offensive reactions from the other interlocutor. The main purpose of this study is to address the politeness strategy use in Buginese Language with special reference to Anregurutta Pappandangan Maros of South Sulawesi. The present research has been set up to account for an ethnographic research and as such research instruments were strictly employed to comply with the nature of resarch design. These include field notes, direct observation, idepth interviews, and recordings. Data were mostly gathered from Anregurutta and the rest from the local people mostly by means of recording and interviews. Greater proportion of the recorded data were from Anregurutta whose daily language of interactional conversation is in Buginese. The recorded conversations were analyzed by means of descriptive analysis and interpretative paradigm.The analysis came up with a series of findings that partly confirm the validity of previous politeness framework, such as Brown and Levinson (1978), and Yassi (1996) with reference to Kinship (K), Distance (D) and Power (P). The finding deviates from the universality of politeness pattern that confirm use of bald-on strategy in non-kinship relation. It appears from the study, bald-on strategy was consistently used in kinship pattern, such as Anregurutta and his wife and daughter. (4.1.5 and 4.1.8). This research gap is most probably due to changes in interactional paradigm as a reult of religious values that has affected the way kindship family interacts. The second finding that has been neglected in the study of poliness of which contributes as the research gap is in reference to metalinguistic of politeness that count spritualism and Islamic suphism as generating motives of having to be polite to other people. The finding may contribute the the development of pragmatics with special reference to politeness strategy in non-european context since these aspects have been neglected in previous studies.